THE PEQUI (Caryocar brasiliense) AND ITS MAIN CHARACTERISTICS (REMUNOM, 2024)
Pequi (Caryocar brasiliense), whose nomenclature comes from Tupi and means “thorny shell”, is a fruit from the Brazilian Cerrado with great prominence in different areas, owing to its numerous potential uses and chemical characteristics. This work highlights that pequi is one of the main fruits of the Cerrado, a biome that occupies 24% of Brazilian territory, with unique plants and species. The Cerrado has 12 distinct types of flora and is characterized by twisted trees, small shrubs, and deep-rooted plants. Pequi has more than 14 different species and is spread across different states of Brazil. Moreover, pequi trees can reach up to 10 meters in height and produce 2.000 fruits per harvest. Pequi is rich in fibers, lipids, calories, vitamins, and minerals. This fruit is capable of supporting the livelihood of various families, and a very importants product extracted from it is pequi oil, wich has antioxidant and anti-inflammatory propeties. It was also concluded that the wood from the pequi tree can be used in naval and construction industries. Additionally, the wood is used as raw material in art and craftsmanship productions. Thus, it is clear that pequi is a valuable fruit for its diverse uses, wheather in gastronomy, society, the economy, or agriculture. It is also a source of food and a possible habitat for different species. Finally, it was concluded that pequi has a significance and utility in human biodiversity and life in the Brazilian Cerrado.